2021
DOI: 10.3390/ph14070680
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Baricitinib as a Repurposed Therapy for COVID-19

Abstract: The emergence of the COVID-19 pandemic has mandated the instant (re)search for potential drug candidates. In response to the unprecedented situation, it was recognized early that repurposing of available drugs in the market could timely save lives, by skipping the lengthy phases of preclinical and initial safety studies. BenevolentAI’s large knowledge graph repository of structured medical information suggested baricitinib, a Janus-associated kinase inhibitor, as a potential repurposed medicine with a dual mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Baricitinib (olumiant) is a selective JAK1/2 inhibitor that was approved for anti-TNF-α-resistant RA patients [121] , [122] . Recently, it has also been shown to hinder the endocytosis and assembly of the SARS-CoV-2 to the host cell by inhibiting AP2-associated protein kinase 1 (AAK1) [123] , [124] , [125] . Considering the inhibitory effects of baricitinib on the JAK-mediated inflammatory process and the entrance of SARS-CoV-2 to the host cell, it has been thought to be investigated in COVID-19 patients to improve the cytokine storm [126] , [127] , [128] .…”
Section: Inhibition Of Il-6 In Covid-19mentioning
confidence: 99%
“…Baricitinib (olumiant) is a selective JAK1/2 inhibitor that was approved for anti-TNF-α-resistant RA patients [121] , [122] . Recently, it has also been shown to hinder the endocytosis and assembly of the SARS-CoV-2 to the host cell by inhibiting AP2-associated protein kinase 1 (AAK1) [123] , [124] , [125] . Considering the inhibitory effects of baricitinib on the JAK-mediated inflammatory process and the entrance of SARS-CoV-2 to the host cell, it has been thought to be investigated in COVID-19 patients to improve the cytokine storm [126] , [127] , [128] .…”
Section: Inhibition Of Il-6 In Covid-19mentioning
confidence: 99%
“…CCL4 and family members of tumor necrosis factor (TNF, TNFSF11) were enriched. Baricitinib treatment appears to suppress tissue regeneration, ion, and membrane transduction, as well as cellular responses ( 159 ). A study by Hasan et al showed that baricitinib could potentially suppress inflammatory cascades in severe COVID-19 pneumonia.…”
Section: Jak Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%
“…Interestingly, a study of individuals treated with baricitinib found that ACE2 and TMPRSS2 levels were significantly reduced. In addition, baricitinib inhibits the AAK2 virus by binding to anesthetics-related kinases, and GAK-induced endocytosis, ultimately reducing the viral load ( 159 ). The ability of baricitinib to reduce the production of these cytokines, and hence immunological factors, has been demonstrated to aid patients with COVID-19 dramatically.…”
Section: Jak Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%
“…Furthermore, transcriptomic analysis of baricitinib-treated model reveals a significant downregulation of ACE2, and TMPRSS2 in patients treated with baricitinib, thus slowing the entry of SARS-CoV-2 into target cells. 265 Moreover, through binding to numb-associated kinases, baricitinib further inhibits AAK1, and GAK-mediated endocytosis of the virus-ACE complex, thus leading to a reduction in the viral load. 266 Notewothy, baricitinib at therapeutically clinically-relevant levels has been shown to reduce infectivity of Covid-19 in human primary liver spheroid model.…”
Section: Baricitinibmentioning
confidence: 99%